Nutritional diagnosis of the organic conilon coffee trees (Coffea canephora Pierre ex Froehn): suffiency range approach for leaves and soil - Partelli, Fábio Luiz; Vieira, Henrique Duarte; Martins, Marco Antônio (Coffee Science - ISSN 1984-3909, 2007)
The objective of this study was to establish the Sufficiency Range Approach of both the Foliar (SRAF) and the soil nutrient contents (SRAS) of Conilon coffee trees (Coffea canephora Pierre ex Froehn), cultivated organically in Espírito Santo - Brazil. The nutritional diagnosis using Diagnosis Recommendation Integrated System (DRIS) 1and SRAF, was also compared. The nutrient contents of the leaves and soil were evaluated in 56 organic crops. To establish SRAF and SRAS, the foliar and the soil nutrient contents was used respectively, from 22 crops with high yield (equal or above 2,400 kg ha-1 coffee fruit processing). The comparison between DRIS and SRAF was performed through the ordination of the limiting nutrients and qui-square test. Results revealed that SRAF was of: N (g kg-1) 26.2-29.0, P (g kg-1) 1.51-1.75, K (g kg-1) 14.7-18.7, Ca (g kg-1) 12.4-14.6, Mg (g kg-1) 2.92-4.19- 6, S (g kg-1) 1.85-2.33, B (mg kg-1) 45.5-63.5, Cu (mg kg-1) 11.1-21.1, Fe (mg kg-1) 69.2-155.0, Mn (mg kg-1) 49.6-98.2 and Zn (mg kg- 1) 7.83-9.97. The SRAS was of: P (mg dm-3) 4.67-15.27, K (mg dm-3) 62.7-258.00, Ca (cmolc dm-3) 1.65-3.49, Mg (cmolc dm-3) 0.61- 0.99, S (mg dm-3) 6.94-27.2, B (mg dm-3) 0.43-0.61, Cu (mg dm-3) 0.15-0.43, Fe (mg dm-3) 31.05-100.20, Mn (mg dm-3) 8.78-56.60 and Zn (mg dm-3) 2.35-6.51. In several cases SRAF identified limitations in the organic Conilon coffee productivity that were not identified by DRIS. DRIS indicated limitation when the nutrient was inside of the SRAF. Manganese followed by P, Cu=Fe and N were the nutrients considered as deficient to the yield, when DRIS was used, on the other hand, when the SRAF was used Mn, Ca, Fe and N were considered deficient nutrients.